(untitled) (LEARNing Landscapes, 2016)
Taking the Earth Charter’s preamble as a beginning, this work calls for “ecological thinking” as a way of seeing and interpreting an interdependent world where we seek “to bring forth a sustainable global society founded on respect for nature, universal human rights, economic justice, and a culture of peace.” Incorporating poems and personal reflections, this braided essay grows out of the author’s experiences in Everglades National Park. As defined by Corey (2016), the braided essay offers “various threads of writing...nearly always without overt transition..., “each part having its own meaning, within “an obliquely accumulating larger impact” (pp. 7–8).